الحماية الجنائية للطفل الجانح خلال مرحلتي التحري والتحقيق وفق التشريع الجزائري - رحيم ،عبد الكريم; جفال ،فاطمة الزهراء (جامعة الوادي University of El Oued, 2024)
تماشيًا مع المبادئ العالمية، الداعيّة لإعادة النظر في طُرق مُعاملة الأطفال، خاصّة الذين هم في نِزاع مع القانون، فإنّ المُشرّع الجزائري قام بإصدار قانون خاص سنة 2015خصّ من خِـــلاله فئـــة الأطفال بحماية خاصّة، لاسيّما منهم الأطفال الجانحين، حيث أفــــرَد لهم حماية قانونية، تحميهم خلال كل مراحل المُتابعة القضائية. حيث تهدف دراستنا الحالية، الى تسليط الضوء على الحماية القانونية، التي أقـــرّها المُشرّع الجزائري للطفل الجانح ،خلال مرحلتي التحري والتحقيق، من خلال دراسة مختلف النصوص القانونية في هذا الشأن، تم الاعتماد على المنهج التحليلي للنصوص القانونية المتعلقة بموضوع حماية الطفل الجانح، مع المنهج الوصفي، من خلال تحديد المفاهيم المتعلقة بالدراسة، إلى المنهج المقارن عند الإستدلال بالنصوص القانونية، من الإتفاقيات الدولية، أين خلُصت نتائج الدراسة الى أن المشرع الجزائري، خصّ فئة الأطفال الجانحين ، بقواعد قانونية خاصّة ومُتميّزة ترُاعي طبيعة تكوينهم الجسدي والعقلي، ألــزم بها جهات الضبط القضائي وجهات التحقيق، واضعًا المصلحة الفُضلى للطفل، أساساً لكل إجراء قد يُتخذ ضده، جاعلاً الإجراءات الماسة بالحرّية كإستثناءً، وملاذاً أخير، وفي نطاقٍ ضيق جــداً، فاسحًا المجال لتدابير الحماية و التهذيب كأولوية. In line with international principles, which call for reconsidering the ways of treating children, especially those in conflict with the law, the Algerian legislator issued a special law in 2015, allocating special protection to a group of children, especially delinquent children, as it provided them with legal protection that protects them during. All stages of judicial follow-up. Our current study aims to shed light on the legal protection approved by the Algerian legislator for the delinquent child during the investigation and investigation stages, by studying the various legal texts in this regard. The analytical approach was based on the legal texts related to the subject of protecting the delinquent child, with the descriptive approach by identifying Concepts related to the study, to the comparative approach when inferring legal texts from international agreements, where did the results of the study conclude that the Algerian legislator allocated the category of delinquent children to special and distinct legal rules that take into account the nature of their physical and mental formation obligating judicial control authorities and investigation authorities, placing the best interest of the child at the basis of every measure that may be taken against him, making measures that infringe on freedom an exception and a last resort and within a very narrow scope , making room for protection and refinement measures as a priority
ماستر جريمة وأمن